THE EFFECT OF CLINICAL COMPETENCE AND WORKLOAD ON THE QUALITY OF NURSING CARE AND NURSE PERFORMANCE IN HOSPITALS: A LITERATURE REVIEW - Siti Hurin Ain; Pipit Festi Wiliynarti (Journal of Public Health Science, 2026)
Service quality is a fundamental indicator in evaluating hospital performance. Nurses have frequent interaction with patients, so the quality of nursing care is the primary determinant of hospital service quality. This study aims to identify the influence of clinical competence and workload on the quality of nursing care and nurse performance in hospitals through literature analysis. The design uses a literature review approach guided by the PRISMA procedure. Articles are collected using search engines such as PubMed, ScienceDirect, and Google Scholar. The articles used were published from 2018-2025 that met the inclusion and exclusion criteria (n=14). Based on the collected articles, high workload is associated with low self-efficacy, fatigue, and decreased nursing competence, which negatively affect nurses' quality and performance. A competent nurse manager effectively improves the nurses' work environment, reduces missed care, and improves the quality of care. Some studies report the positive effects of clinical competence and motivation on nursing performance. In contrast, the effects of workload vary; some studies have not found a significant direct impact due to adaptive factors (n=3). Excessive workload increases emotional fatigue, which mediates a decrease in the quality of care. Clinical competence and workload are the main factors affecting the quality of nursing care and nurses' performance in hospitals. High clinical competence optimizes task execution and patient recovery; conversely, excessive workload leads to chronic fatigue, which then reduces the quality of care and nursing performance.